Subfoveal triamcinolone acetonide following macular hole surgery - Jindal, A; Bhawdekar, A; Pathengay, A (Nepalese Journal of Ophthalmology, 2013)
Background: Triamcinolone acetonide (TA) is commonly used in vitreous surgery to visualize the posterior hyaloid and internal limiting membrane. Some TA can accumulate in the macular hole during surgery which can persist postoperatively. Case: A 17-year-old boy underwent successful macular hole surgery with TA-assisted induction of posterior vitreous detachment. Sub-foveal deposit of TA was observed postoperatively, which got absorbed at 7 weeks with complete closure of the macular hole, and best corrected visual acuity improved from 20/100 preoperatively to 20/60. Conclusion: Residual TA after macular hole surgery may not hamper the anatomical and functional outcome. Similar cases have been reported in the literature and most of them show no harmful effect of TA on macular hole closure and visual recovery. Nepal J Ophthalmol 2013; 5(9):114-116 DOI: http://dx.doi.org/10.3126/nepjoph.v5i1.7837